Transforming growth factor beta induces the cyclin-dependent kinase inhibitor p21 through a p53-independent mechanism. - Datto, M B (1995)
The transforming growth factor beta s (TGF-beta s) are a group of multifunctional growth factors which inhibit cell cycle progression in many cell types. The TGF-beta-induced cell cycle arrest has been partially attributed to the regulatory effects of TGF-beta on both the levels and the activities of the G1 cyclins and their kinase partners. The activities of these kinases are negatively regulated by a number of small proteins, p21 (WAF1, Cip1), p27Kip1, p16, and p15INK4B, that physically associate with cyclins, cyclin-dependent kinases, or cyclin-Cdk complexes. p21 has been previously shown to be transcriptionally induced by DNA damage through p53 as a mediator. We demonstrate that TGF-beta also causes a rapid transcriptional induction of p21, suggesting that p21 can respond to both intracellular and extracellular signals for cell cycle arrest. In contrast to DNA damage, however, induction of p21 by TGF-beta is not dependent on wild-type p53. The cell line studied in these experiments, HaCaT, contains two mutant alleles of p53, which are unable to activate transcription from the p21 promoter when overexpressed. In addition, TGF-beta and p53 act through distinct elements in the p21 promoter. Taken together, these findings suggest that TGF-beta can induce p21 through a p53-independent pathway. Previous findings have implicated p27Kip1 and p15INK2B as effectors mediating the TGF-beta growth inhibitory effect. These results demonstrate that a single extracellular antiproliferative signal, TGF-beta, can act through multiple signaling pathways to elicit a growth arrest response.